2012
DOI: 10.1021/la204164q
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Studies of Carbon Dioxide Intercalation in Na-Fluorohectorite Clay at Near-Ambient Conditions

Abstract: We show experimentally that gaseous CO2 intercalates into the interlayer space of the synthetic smectite clay Na-fluorohectorite at conditions not too far from ambient. The mean interlayer repetition distance of the clay when CO2 is intercalated is found to be 12.5 Å for the conditions -20 °C and 15 bar. The magnitude of the expansion of the interlayer upon intercalation is indistinguishable from that observed in the dehydrated-monohydrated transition for H2O, but the possibility of water intercalation is rule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
45
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 24 publications
8
45
1
Order By: Relevance
“…The adsorption of CO 2 in clay nanopores has been mainly considered in the absence of water. Experimentally, the incorporation of CO 2 in pyrophyllite during dehydroxylation has been observed by infrared spectroscopy (Wang et al 2003) and X-ray diffraction has allowed following the intercalation of CO 2 in Na-fluorohectorite near ambient conditions: the expansion in basal spacing is similar to that obtained during intercalation with water, but it occurs at a rate that is several orders of magnitude slower (Hemmen et al 2012). The density of CO 2 confined in Na-montmorillonite with a sub-single hydration layer depends on the bulk scCO 2 density (Rother et al 2013).…”
Section: Co 2 -Brine-mineral Systems With a Single Fluid Phasementioning
confidence: 98%
“…The adsorption of CO 2 in clay nanopores has been mainly considered in the absence of water. Experimentally, the incorporation of CO 2 in pyrophyllite during dehydroxylation has been observed by infrared spectroscopy (Wang et al 2003) and X-ray diffraction has allowed following the intercalation of CO 2 in Na-fluorohectorite near ambient conditions: the expansion in basal spacing is similar to that obtained during intercalation with water, but it occurs at a rate that is several orders of magnitude slower (Hemmen et al 2012). The density of CO 2 confined in Na-montmorillonite with a sub-single hydration layer depends on the bulk scCO 2 density (Rother et al 2013).…”
Section: Co 2 -Brine-mineral Systems With a Single Fluid Phasementioning
confidence: 98%
“…Giesting et al (2012a) and Hemmen et al (2012) also proposed CO 2 intercalation of montmorillonite under supercritical as well as sub-critical conditions based on in situ XRD experiments. More recently, swelling strain experiments with nearly dry montmorillonites produced volume changes in the presence of scCO 2 leading to possible implications about reservoir permeability (de Jong et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…1,6,[18][19][20][21][22][23][24][25][26][27][28][29]38,57,58,60,[64][65][66][67] Because of their common natural occurrence, they may also play an important role in geological CO 2 -sequestration reservoirs. 1,6,[18][19][20][21][22][23][24][25][26][27][28][29]38,67,57,58,60,[64][65][66][67] The affinity and specificity of oxide surfaces for intercalates can be controlled by a variety of compositional and structural parameters including substitutions in the tetrahedral and octahedral layers, variability in charge-balancing cations, and coatings of functionalized organic compounds. [38][39][40]...…”
mentioning
confidence: 99%
“…43,[48][49][50][68][69][70][71][72][73] With respect to CO 2 incorporation in smectite interlayer galleries, several recent in situ high-pressure and temperature experimental X-ray diffraction, Infrared (IR), and NMR studies have shown that CO 2 enters the interlayer galleries at supercritical CO 2 -sequestration reservoir conditions and affects the structural environments and dynamics of interlayer cations. [18][19][20][21][22][23][24][25][26][27][28][29]58 For instance, Schaef et. al., 62 estimated the amount of CO 2 in the interlayer of dry sodium montmorillonite (Na-MMT) using quartz crystal microbalance (QCM) measurements while Loring et.…”
mentioning
confidence: 99%